Book review: Lithic Materials and Paleolithic Societies - Christopher D. Noll (Journal of Lithic Studies, 2015)
Lithic Materials and Paleolithic Societies is an edited volume of research papers that provides perspectives on the study of lithic technological organization from around the world. The book contains 20 chapters organized into four thematic sections focused on stone procurement, tool-stone use, the role of tool-stone subsistence and settlement systems, and the clues about social interaction that are gleaned from the study of lithic materials.